KAJIAN KELEMBAGAAN AGRIBISNIS WORTEL UNTUK MENDUKUNG PENGEMBANGAN KAWASAN AGROPOLITAN SUTHOMADANSIH DI KABUPATEN KARANGANYAR - Sutarto Sutarto; Dwiningtyas Padmaningrum; Agung Wibowo (Caraka Tani: Journal of Sustainable Agriculture, 2010)
So far, development of rural agribusiness institutions is commonly far from expectation to solve related problems. The model of partnership between farmers and agribussiness entrepreneurs indicated an unsatisfactory performance. The underdevelopment of the partnership’s model was due to philosophically, it had not united stakeholders within a common purpose which provided benefits proportionally. The objective of the research aimed at (i) describing the local agribussines institution having potential to suppot a carrot agribussiness; (i) to assess the local institutional performance in order to support a carrot agribussiness; (ii) to examine the opinion of its stakeholders towards institutional development for carrot. This study used a descriptive method. The location have been selected purposively. The Subdistrict of Tawangmangu had been selected as the produce of carrot was the highest compared to other subdistricts in District of Karanganyar. The information was collected from a number of key informants. The informants get confused about the concept of ‘agropolitant itself; even some of the farmers did not care about that concept. Area of agropolitant which formerly planned to become agro-tourism and the promotion of the local product was regarded far from expectation. In fact, there was no marketing activities for those local products. Some programs was considered to be reasonable to implement in order to achieve the objectives. First, in order to improve the bargaining positions, it was reasonable to increase the intensity of asssistance. Particularly, it was suggested to increase the quality of organization management and entreprenurship. Second, it is necessary for the local government to facilitate the networks among the subdistricts or with outer districts with special attention to connect the carrot farmers. As the institution which is commodity base is effective for implementing the function of development, advocation, and promotion relevant to carrot. Third, there is necessary for local government to improve the effectiveness, especialy at the stage of socialization, in regard with the agropolitant development.